Leaching response of coastal sandy soils to subsurface hybrid ameliorant layering across homogeneous land units - Utami, Sari Widya; Fadillah, Fadillah; AJi, Galih Mustiko (Brawijaya University, 2026)
Sandy soil is characterized by a coarse texture, low organic content, low water-holding capacity, and rapid leaching. Soil amendments are usually applied to improve soil physicochemical characteristics, but their effects are only short-term. Subsurface hybrid ameliorant layering has been proposed as a means to reduce leaching in sandy soils. This study evaluated the leaching responses to subsurface hybrid ameliorant placement within the soil, using a soil column experiment with two factors: kinds of HLU (Homogeneous Land Unit) as the first factor, which consisted of eight HLUs, and ameliorant placement treatments as the second factor, which consisted of control treatment, conventional placement, and subsurface placement. The leaching response parameters were cumulative leachate volume and the differences in organic carbon, nitrogen, and phosphorus concentrations between the upper and bottom layers. The results showed that subsurface placement can reduce the cumulative leachate volume and increase N concentration in the upper layer after the incubation period, but did not significantly affect organic carbon or phosphorus availability in either layer. The application of this treatment resulted in different responses among HLUs, which were influenced by the natural physicochemical characteristics of the soil.